Sustainable Development Mechanism of Avoiding Group Conflict and Symbiosis: A Study on Labor Disputes. (3rd November 2019) - Dong, Jing; Shen, Huizhang; Zhao, Jidi
Abstract : Group conflict is one of the main human conflicts in the history of human development and results in various forms such as competition, fight, riot, or war in extreme cases and compromise, negotiation, or cooperation in other cases. The inner essence of the group conflict is competitors vying for resource control. If the conflict ends up at a situation where one party overwhelms the other, it will actually bring destructive results to both sides. Is there a solution to avoid fierce conflicts and to achieve a win-win situation? Is there a unified model by which different forms of conflicts can be interpreted and studied? The purpose of this paper was to address these problems and attempt to establish such a unified model and to use it to analyze the dynamic relationship between the employees and their employers in the viewpoint of group conflict and symbiosis. By changing coefficients of the unified model, the two sides, employers and employees, could be in different situations such as employer win, employee win, lose-lose, and win-win. Keeping other coefficients unchanged, we found and proved that there is a win-win strategy space of the payoff rate. Two parties chose strategy within the space can achieve optimal status in long run.